Hydrogen peroxide influence on contractile activity smooth muscle cells: the role of cytoskeleton - I. V. Kovalyev; S. V. Gusakova; O. S. Melnik; M. B. Baskakov; L. V. Kapilevich; M. A. Medvedev; V. B. Studnitsky; O. I. Antonov (Бюллетень сибирской медицины)
The influence of of hydrogen peroxide on the contractile reactions of smooth muscle cells caused by hyperpotassium solution end phenylephrine in modulation a potassium conductance the membrane and the state of cytoskeleton elements has been investigated by the mechanographical method. It has multidirectional influence of hydrogen peroxide in the reduction of smooth muscles of rat aorta with the membrane depolarization hyperpotassium solution and action phenylephrine: phenylephrine decline in value and increase strength hyperpotassium contractures. We show that the cytoskeleton components involved in the mechanisms of action of hydrogen peroxide in the contractile reactions of smooth muscles of rat aorta caused by phenylephrine.